Existence of positive radial solutions for a weakly coupled system via blow up - Marta García-Huidobro; Ignacio Guerra; Raúl Manásevich (Abstract and Applied Analysis)
The existence of positive solutions to certain systems of ordinary differential equations is studied. Particular forms of these systems are satisfied by radial solutions of associated partial differential equations.